Study on tar generated from downdraft gasification of oil palm fronds - Atnaw, S.M. (2014)
One of the most challenging issues concerning the gasification of oil palm fronds (OPF) is the presence of tar and particulates formed during the process considering its high volatile matter content. In this study, a tar sampling train custom built based on standard tar sampling protocols was used to quantify the gravimetric concentration of tar (g/Nm3) in syngas produced from downdraft gasification of OPF. The amount of char, ash, and solid tar produced from the gasification process was measured in order to account for the mass and carbon conversion efficiency. Elemental analysis of the char and solid tar samples was done using ultimate analysis machine, while the relative concentration of the different compounds in the liquid tar was determined making use of a liquid gas chromatography (GC) unit. Average tar concentration of 4.928 g/Nm3 and 1.923 g/Nm3 was obtained for raw gas and cleaned gas samples, respectively. Tar concentration in the raw gas sample was found to be higher compared to results for other biomass materials, which could be attributed to the higher volatile matter percentage of OPF. Average cleaning efficiency of 61 which is comparable to that of sand bed filter and venturi scrubber cleaning systems reported in the literature was obtained for the cleaning system proposed in the current study. Â© 2014 Samson Mekbib Atnaw et al.